Faktor-faktor yang mempengaruhi Perilaku Administrasi Publik: Kecerdasan Emosional, Profesionalisme dan Disiplin Kerja - Denisa Salsabila Viyanis; Cris Kuntadi (Institut Nalanda, 2023)
Administrative behavior is a person's choice to carry out administrative activities, such as providing intensive services, with a focus only on achieving predetermined organizational goals. The study of cooperation in public organizations is called public administration. Because public administration is a branch of administrative science, all theories, concepts and analyzes of administrative science are used. In the research literature on organizational behavior, this article examines the following factors in public administration behavior: emotional intelligence, professionalism, and work discipline. Developing hypotheses regarding these variables is the goal of this paper. This hypothesis can be used in future research. The results of this review article are: Emotional Intelligence influences Public Administration Behavior, Professionalism influences Public Administration Behavior and Work Discipline influences Public Administration Behavior.